(untitled) (Journal of Informatics Education and Research, 2025)
This study provides a comparative analysis of talent management strategies in the top 10 IT companies in India, ranked by market capitalization, focusing on employee headcount, attrition rates, learning and development initiatives, employee engagement, career growth opportunities, diversity and inclusion practices, and work-life balance programs. The study examines the correlation between talent management initiatives and employee retention, along with the effectiveness of recruitment strategies based on return on investment (ROI). By evaluating how these factors influence employee turnover, satisfaction, and productivity, the research aims to offer valuable insights into how these firms manage their talent and how it impacts their overall business performance.